Expression of Transketolase like gene 1 (TKTL1) predicts disease-free survival in patients with locally advanced rectal cancer receiving neoadjuvant chemoradiotherapy - Schwaab, Juliana; Horisberger, Karoline; Ströbel, Philipp; Bohn, Beatrice; Gencer, Deniz; Kähler, Georg; Kienle, Peter; Post, Stefan; Wenz, Frederik; Hofmann, Wolf-Karsten; Hofheinz, Ralf-Dieter; Erben, Philipp (BMC cancer, 2011)
For patients with locally advanced rectal cancer (LARC) neoadjuvant chemoradiotherapy is recommended as standard therapy. So far, no predictive or prognostic molecular factors for patients undergoing multimodal treatment are established. Increased angiogenesis and altered tumour metabolism as adaption to hypoxic conditions in cancers play an important role in tumour progression and metastasis. Enhanced expression of Vascular-endothelial-growth-factor-receptor (VEGF-R) and Transketolase-like-1 (TKTL1) are related to hypoxic conditions in tumours. In search for potential prognostic molecular markers we investigated the expression of VEGFR-1, VEGFR-2 and TKTL1 in patients with LARC treated with neoadjuvant chemoradiotherapy and cetuximab.